2011
DOI: 10.1089/hum.2010.118
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of a Recombinant Adeno-Associated Virus Vector Expressing Human Alpha-1 Antitrypsin Made Using a Recombinant Herpes Simplex Virus Production Method

Abstract: Recombinant adeno-associated virus (rAAV) vectors offer promise for gene therapy of alpha-1 antitrypsin (AAT) deficiency. A toxicology study in mice evaluated intramuscular injection of an rAAV vector expressing human AAT (rAAV-CB-hAAT) produced using a herpes simplex virus (HSV) complementation system or a plasmid transfection (TFX) method at doses of 3Â10 11 vg (1.2Â10 13 vg/kg) for both vectors and 2Â10 12 vg (8Â10 13 vg/kg) for the HSV-produced vector. The HSV-produced vector had favorable in vitro charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 34 publications
3
59
0
Order By: Relevance
“…22 Concentrations of BHK protein, bovine serum albumin, Benzonase, and AVB ligand were measured by enzyme-linked immunosorbent assay (ELISA) using commercially available kits. HSV and BHK DNA were measured by qPCR.…”
Section: Vector Characterizationmentioning
confidence: 99%
“…22 Concentrations of BHK protein, bovine serum albumin, Benzonase, and AVB ligand were measured by enzyme-linked immunosorbent assay (ELISA) using commercially available kits. HSV and BHK DNA were measured by qPCR.…”
Section: Vector Characterizationmentioning
confidence: 99%
“…26,27 The HSV complementation system for vector production was validated in a mouse toxicology study comparing it to the previously used traditional transfection method and found that the HSV vector system had increase packaging efficiency as well as increased in vivo vector expression and a similar safety profile as traditionally produced vector. 28 The phase 2 clinical trial consisted of 3 dose cohorts of rAAV1-CB-hAAT at 6 · 10 11 , 1.9 · 10 12 , or 6 · 10 12 vg/kg, with 3 patients per cohort. The total dose in this study ranged from 3.3 · 10 14 to 4.3 · 10 14 vg per subject.…”
Section: Phase 1 Clinical Trial: Aav1 (Published 2009)mentioning
confidence: 99%
“…Despite encouraging results in animal models, amended by confirmation in three clinical and one preclinical study (25)(26)(27)(28), its use in the treatment of pulmonary manifestations has not been officially approved yet. Up to now, the efficiency of gene therapy in the prevention of accumulation of »mutated« AAT molecules in hepatocytes has been tested only in animal models, and beside positive results, additional toxic effects have also been revealed (24).…”
Section: Therapeutic Approach In Aatdmentioning
confidence: 99%